A Demonstrative Analysis of News Articles Using Faircloughâ€™s Critical Discourse Analysis Framework - Briones, Roy Randy Y. (Widya Mandala Catholic University Surabaya, 2017)
This paper attempts to demonstrate Norman Faircloughâ€™s Critical Discourse Analysis (CDA) framework by conducting internal and external level analyses on two online news articles that report on the Moro Islamic Liberation Frontâ€™s (MILF) submission of its findings on the â€œMamasapano Incidentâ€ that happened in the Philippines in 2015. In performing analyses using this framework, the social context and background for these texts, as well as the relationship between the internal discourse features and the external social practices and structures in which the texts were produced are thoroughly examined. As a result, it can be noted that from the textsâ€™ internal discourse features, the news articles portray ideological and social distinctions among social actors such as the Philippine Senate, the SAF troopers, the MILF, the MILF fighters, and the civilians. Moreover, from the viewpoint of the texts as being external social practices, the texts maintain institutional identities as news reports, but they also reveal some evaluative stance as exemplified by the adjectival phrases that the writers employed. Having both the internal and external features examined, it can be said that the way these texts were written seems to portray power relations that exist between the Philippine government and the MILF. Key words: Critical Discourse Analysis, discourse analysis, news articles, social practices, social structures, power relations